In search of anthropology in metaphysics of Alfred North Whitehead - Jaworski, Jacek (Folia Philosophica, 2010)
My aim in this paper is to try to encapsulate a selection of issues typical for philosophical anthropology from the standpoint of Alfred North Withehead’s metaphysics. Whitehead himself has not presented any developed anthropological theory. Yet, if his metaphysical theory is supposed to give possibility of interpretation of every element of possible experience, it might be also useful to provide a new research perspective for anthropology. For this reason I start with a brief discussion of Whitehead’s metaphysics: the actual entity (one of Whitehead’s key categories), descriptions of the process of unifying of actual entity and the dynamic structure of living organism (including man). Finally, I attempt to analyse certain issues of philosophical anthropology from this perspective: personal immortality, identity, freedom and man’s openness to the world.